Analisis Pengaruh Pola Konsumsi, Persepsi Pemenuhan Pangan, dan Persepsi Gizi terhadap Ketahanan Pangan Rumah Tangga di Kabupaten Kotawaringin Barat - Hasaruddin; Siti Khotimah (Bajang Institute, 2026)
Abstrak: Food security at the household level is an important indicator of community welfare, influenced not only by physical food availability but also by consumption patterns and public perceptions of food fulfillment and nutrition. This study aims to analyze the influence of food consumption patterns, perceptions of food fulfillment, and nutritional perceptions on household food security in Kotawaringin Barat Regency. Using a quantitative approach with multiple linear regression analysis involving 100 respondents, the results show that all three independent variables simultaneously have a positive and significant effect on household food security (F = 67.602, p = 0.000), explaining 67.9% of its variation. Partially, food consumption patterns (B = 0.342, p = 0.000), perceptions of food fulfillment (B = 0.287, p = 0.000), and nutritional perceptions (B = 0.415, p = 0.000) each have a positive and significant influence, with nutritional perception emerging as the most dominant factor. It is concluded that household food security in Kotawaringin Barat is shaped by a combination of healthy consumption habits, confidence in food fulfillment, and awareness of nutritional importance, suggesting that improving nutritional understanding should be prioritized in efforts to strengthen household food security.